Unfinished Past : Coming to terms with the Second World War in the Visual Arts of Germany and the Netherlands. - Alderse Baas, Willem; Alderse Baas-Budwilowitz, Peggy; Fischer, Gottfried; Grisebach, Lucius; Segal, Joes; de Haan, Ido; Neues Museum - Staatliches Museum für Kunst und Design, Nürnberg; Pulchri Studio, Den Haag (Amsterdam : Art and Society Foundation, 2000)
Altenbourg, Gerhard ; Armando ; Baselitz, Georg ; Böttcher,Strawalde, Jürgen ; Chabot, Hendrik ; Constant ; Couzijn, Wessel ; Heidt, Werner ; Katzir, Ram ; Kiefer, Anselm ; Kippenberger, Martin ; Lüpertz, Markus ; Mulders, Marc ; Rheinsberg, Raffael ; Richter, Gerhard ; Schoonhoven, Jan ; Tajiri, Shinkichi ; Uecker, Günther ; Werkman, Hendrik N.
biog., bibliog. p. 126-144
Engels & Duits
Unfinished Past / Unvollendete Vergangenheit, Neuesmuseum - Staatliches Museum für Kunst und Design in Nürnberg, 24. September to 26. December 2000 ; Pulchri Studio, Den Haag, 6 January to 26 February 2001
boek
Keywords: Duitsland; Nederland